2015
DOI: 10.7763/ijssh.2015.v5.411
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional Intelligence and Teaching Effectiveness among Lecturers at Universiti Teknologi MARA, Puncak Alam, Malaysia

Abstract: Abstract-In this study, the researchers examined the relationship between emotional intelligence (EI) and teaching effectiveness among lecturers at Universiti Teknologi MARA (UiTM), Puncak Alam, Selangor. The participants consisted of 155 lecturers working at UiTM, Puncak Alam, Selangor. The respondents were randomly selected and the data were gathered through the distribution of questionnaires. Descriptive statistics showed that there were more female than male faculty members and majority of them were from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
5
17
1
Order By: Relevance
“…This study had shown that high EI is associated with cortisol levels and lower blood pressure. This is really important for physical health (Salovey, Mayer, Goldman, Turvey, & Palfai, 1995;(Hassan, Jani, Som, Hamid, & Azizam, 2015). Also the results of this study are consistent with Ghorbani et al and Farahbakhsh et al results (Farahbakhsh, 2012;Ghorbani, Bing, Watson, Davison, & Mack, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…This study had shown that high EI is associated with cortisol levels and lower blood pressure. This is really important for physical health (Salovey, Mayer, Goldman, Turvey, & Palfai, 1995;(Hassan, Jani, Som, Hamid, & Azizam, 2015). Also the results of this study are consistent with Ghorbani et al and Farahbakhsh et al results (Farahbakhsh, 2012;Ghorbani, Bing, Watson, Davison, & Mack, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…This learning approach aims to gain an effective process of promoting engagement and discussion, concerning, respecting, and maximizing an academic achievement (Aregbeyen, 2010;Hassan et al, 2015). So, students may think about how a certain concept is expressed in a various discussion session within the classroom or the small groups (Ellis, 2012).…”
Section: A Influencing Factors Of Divergent Approachmentioning
confidence: 99%
“…Murphy and Sharma (2010) agree that this approach can be developed into a full discussion, which enables students to facilitate the group feedback in the discussion spontaneously. This learning approach aims to gain an effective process of promoting engagement and discussion, concerning, respecting, and maximizing an academic achievement (Aregbeyen, 2010;Hassan et al, 2015). So, students may think about how a certain concept is expressed in a various discussion session within the classroom or the small groups (Ellis, 2012).…”
Section: A Influencing Factors Of Divergent Approachmentioning
confidence: 99%
“…The awareness skills allow students to promptly establish and comfortably maintain the effective interpersonal relationships with individuals and groups (Nelson & Low, 2003;Hassan et al, 2015) by underlying the language systems that enable them to learn and to practice effectively (Andrews, 2007).…”
Section: A Influencing Factors Of Divergent Approachmentioning
confidence: 99%